Changing treatment landscape associated with improved survival in advanced hepatocellular carcinoma: a nationwide, population-based study - Ben Khaled, Najib; Mörtl, Bernhard; Beier, Dominik; Reiter, Florian P.; Pawlowska-Phelan, Dorota; Teufel, Andreas; Rössler, Daniel; Schwade, Daniel F.; Philipp, Alexander; Kubisch, Ilja; Ehmer, Ursula; Geier, Andreas; et al. (European journal of cancer, 2023)
Background and Aims - The treatment of hepatocellular carcinoma (HCC) is undergoing a historic transformation with the approval of several new systemic therapies in the last few years. This study aimed to examine the impact of this changing landscape on survival and costs in a Western nationwide, real-world cohort. - Methods - A nationwide representative claims database (InGef) was screened for HCC cases between 2015 and 2020. Survival in an era with only sorafenib (period A, January 2015 to July 2018) and after approval of lenvatinib and other systemic treatments (period B, August 2018 to December 2020) was analysed. Health care costs were assessed. - Results - We identified 2876 individuals with HCC in the study period. The proportion of patients receiving systemic therapy increased significantly over time, from 11.8% in 2015 to 15.1% in 2020 (p < 0.0001). The median overall survival in period B was 6.5 months (95% confidence interval [CI]: 4.9-8.9) and in period A was 5.3 months (95% CI: 4.5-6.3; p = 0.046). In period B, the median overall survival with lenvatinib was 9.7 months (95% CI: 6.3-18.4) versus 4.8 months with sorafenib (95% CI: 4.0-7.1, p = 0.008). Costs for prescription drugs per patient increased from €6150 in 2015 to €9049 in 2020 (p < 0.0001), and costs for outpatient care per patient increased from €1646 to €2149 (p = 0.0240). - Conclusion - The approval of new systemic therapies resulted in a survival benefit in patients with HCC. The magnitude of the effect is modest and associated with a moderate increase in health costs.
Online verfügbar: 21. Juli 2023, Artikelversion: 4. September 2023
Gesehen am 07.12.2023